Description of a new species of Oligosita Walker (Chalcidoidea: Trichogrammatidae), egg parasitoid of Balclutha brevis Lindberg (Homoptera: Cicadellidae) living on Pennisetum setaceum, from Italy - Bella, Salvatore; Cupani, Sebastiano; D’urso, Vera; Laudonia, Stefania; Sinno, Martina; Viggiani, Gennaro (Zootaxa, 2015)
A new species of Oligosita Walker (Chalcidoidea: Trichogrammatidae), O. balcluthae Viggiani et Laudonia n. sp., is described as a parasitoid of the eggs of Balclutha brevis Lindberg (Homoptera: Cicadellidae) associated with crimson fountain grass, Pennisetum setaceum (Poaceae) in Italy. Morphological features and biology of the new species are discussed and illustrated. The 28S-D2 and ITS2 regions were successfully amplified and sequenced.